(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Diabetes mellitus is one of the common problems in Pakistan; it is a disease that is extensively spreading within all age groups. It is a misconception that it suddenly affects a persons metabolism and the next morning the patient becomes diabetic. Actually diabetes gives an intense era of time for recovery which is usually never identified. Aim and Objective: The aim of the study is to identify the time lap known as prediabetes which can also be taken as the prevention stage. Materials and methods: In this study 201 population sample data was collected on the basis of their age, gender, family history , life style and many other contribution factors and analyzed through SPSS. Results: It is concluded that majority of the population belonging to a different age groups are on the route that leads to diabetes and having principle symptoms of diabetes that is polyuria (increased urination), polyphagia (increased appetite), polydypsia (increased thirst), 55% of the individuals experience frequent urination, 58% of the population have been observed with increased appetite and 60% of the people have complains of increased thirst. Conclusion: It is a frightening situation as indicated by the WHO that by 2030 Pakistan will be the 4th most diabetic populated country, so the study played an important role in investigating population lying in prevention stage. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.565-571